PUBLIC HISTORY: AN EFFORT TO INCREASE INDONESIAN HISTORICAL CONSCIOUSNESS DURING COVID-19 PANDEMI - Abdurakhman, Abdurakhman; Rahman, Syahidah Sumayyah (International Review of Humanities Studies, 2021)
The writing of public history has become one of the methods of history that have developed and are in great demand. The difference between history in general and public history is the selection of groups that are used as research sources. Through this research, the author find that public history can be used as a way to raise historical consciousness in Indonesia. Historical Consciousness relates to thinking of ourself in time as historical beings and being aware of belonging to a specific group with a particular history and identity. The current global pandemic presents a challenge for historians. Documenting the history at the time the event was still taking place was a challenge in itself since no one knew how the end of the event was written. Public history has been widely used in European countries to record daily life and events that occurred in society during the pandemic. The historical sources collected from the public will play an important role on writing the historical event and also as a lesson in the future. The method used in this paper is a historical method consisting of 4 stages, namely heuristics, source criticism, interpretation, and then historiography.